Answer:
a = 3, b = 12
Explanation:
x^2-6x-3=(x-a)^2-b
Lets expand the right side:
(x-a)^2-b = (x-a)(x-a)-b
(x-a)(x-a)-b = x^2 -2ax + a^2 - b
The left side is equal to the right, as per the original equation:
x^2-6x-3 = x^2 -2ax + (a^2 - b)
Compare each term:
1) x^2 = x^2 OK
2) -6x = -2ax; a = 3 so that -6x = -2(3)x
3) -3 = (a^2-b); a^2 = (b-3)
a =
![√(b-3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/uq8xgp52tedtmq1vv3995pigjg0vg6hk11.png)
a is 3, from above
3 =
![√(b-3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/uq8xgp52tedtmq1vv3995pigjg0vg6hk11.png)
9 = b-3
b = 12